Employee retention among private hospital nurses: The role of HRM practices - Yahya, Khulida Kirana; Tan, Fee Yean; Sasee, Hemallatha (2017)
The service sector such as the healthcare has been recognized as one of the main contributors to the growth of Malaysian economy. Nurses tend to leave the workplace, nation and even profession because of the amount of healthcare associations and the challenging economic situation of a country.This research is carried out to examine the relationship between compensation and benefits, training and development with employee retention among nurses in a private hospital in Penang.A survey was carried out in a private hospital in Penang. A total of 250 questionnaires were distributed but only 200 questionnaires were returned and utilized for data analysis.Regression analysis results indicate that only compensation and benefits were positively related and have significant relationship with employee retention. Thus, compensation and benefits is considered as the most important variable in influencing the nurses to retain in an organization.